Optimizing the performance of Village-Owned Enterprise: A case study - Alhadi, Iqbal; Wardani, Dea Mustika Kusuma; Khansa, Ezry Zhahri (Co-Creation : Jurnal Ilmiah Ekonomi Manajemen Akuntansi dan Bisnis, 2024)
The implementation of performance measurement systems in public organizations was essential for optimizing task execution, service delivery, and business processes, thereby ensuring the achievement of organizational goals. However, the adoption of such systems in Village-Owned Enterprises (VOEs) across Indonesia remained insufficient. This was reflected in the high number of non-operational VOEs or those contributing minimally to local communities. A key issue was the lack of a strategic performance measurement framework, which hindered these organizations from achieving their vision and mission effectively. This study aimed to develop a performance measurement framework tailored to VOEs using the Balanced Scorecard (BSC) methodology. It employed document reviews, interviews, and analyses of the vision, mission, and strategic objectives of VOE Cimenteng Jaya as a case study. The framework aligned strategic goals with the four BSC perspectives: financial, learning and growth, internal processes, and stakeholders. A strategy map visualized the interconnections among these perspectives. The study identified nine strategic objectives and fifteen Key Performance Indicators (KPIs) relevant to the VOE. By providing a structured approach to performance evaluation, the framework was expected to improve the VOE's contribution to local economic development and community welfare.